The Process of Developing Religious Moderation Values in the Social Interaction of the Bali and Sasak Ethnicity in Lombok - Susilo Edi Purwanto (Jurnal Syntax Admiration, 2023)
The Sasak ethnic group is the central community that inhabits the island of Lombok, which is also an essential part of ethnic diversity in Indonesia. The social interaction between Balinese and Sasak ethnic groups gave rise to many interesting facts regarding diversity, culture, and traditions. This research focuses on the process of developing religious moderation values ​​in the social interactions of the Balinese and Sasak ethnic groups, the forms of religious moderation values ​​in the social interactions of the Balinese and Sasak ethnic groups, and the implications of the values ​​of religious moderation in the social interactions of the Balinese and Sasak ethnic groups. This qualitative research uses non-participant observation data collection methods, semi-structured interviews, and documentation. Data were analyzed through the stages of reduction, exposure, and conclusion. The results of this study are as follows, the process of developing the value of religious moderation in the social interactions of the Balinese and Sasak ethnic groups in Lombok is inseparable from the influence of events in the past, social harmonization between Balinese and Sasak ethnic groups in Lombok is well established, although in the field there are still minor conflicts that occur, they can be appropriately resolved by the relevant stakeholders.